Memory, Symbolic Reparation and Art: Memory as Part of the Truth - Rivera Revelo, Laura (2020)
The article reflects on the duty of the state and Colombian society in the construction of historical and collective memory as part of the duties to the victims of the armed conflict within the framework of integral reparation, the right to the truth and the fulfillment of the measures of satisfaction and non-repetition, in these last two measures emphasizes how art plays a fundamental role in the symbolic reparation, in the recovery of memory and the dignification of the victims of the Colombian armed conflict through photography , painting and counter-monuments.